Analisis Lagu Nasional Sebagai Media Pendidikan Karakter di Sekolah Dasar - Lucky Atminias; Ari Widyaningrum; Eka Sari Setianingsih (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to describe the use of the national anthem as a medium for character education in elementary schools. This research uses descriptive qualitative method. The data analysis technique used was to analyze the data obtained through documentation, observation, interviews, and questionnaires. The results of the study indicate that through the national song as a medium for character education in schools, it can make the character of students better. This is shown from the results of interviews with teachers and school principals who said that the national song can be used as a medium for character education. This statement was strengthened by the results of the distribution of questionnaires to students which showed that 93% stated that the national anthem could be used as character education. The conclusion of this study is that the national anthem is effective as a medium for character education in elementary schools.